Dissecting the metal resistance genes contributed by virome from mining-affected metal contaminated soils - Zhang, Hetian; Huang, Jingyi; Zeng, Weiai; Xiao, Qinzhi; Zhu, Yi; Kong, Wuyuan; Zou, Junliang; Liu, Tianbo; Yin, Huaqun (Frontiers in Environmental Science, 2023)
Virus-borne auxiliary genes have been demonstrated to influence their hosts' characteristics and flexibility, resulting in an elevated ability to withstand diverse conditions and competition. However, not much is known about soil viral communities and their influencing factors. The effects of bacterium-phage co-evolution in the metal contaminated environment have yet to be fully understood. In our research, numerous viral genes with conserved functional residues/motifs working on detoxifying heavy metals were pinpointed in the virome recovered from contaminated soil samples of mineral area, including tellurite resistance genes (e.g. terC, terD), copper resistance genes (e.g. copC, copA), and arsenate resistance genes (e.g. arsC). Moreover, viral proteins involved in key processes of nutrient uptake and metabolism, cellular function, polysaccharides production and biomineralization were also detected, which may also contribute to the response of microbial community to heavy metal stress. Our research showed that viruses have helped their hosts to acquire novel metal-resistance abilities through horizontal gene transfer (HGT) during the adaptation to challenging metal-rich environments. This was also evidenced by the high Codon adaption index (CAI) values across metal-resistance-related genes. This study has advanced our understanding on virus-host interplay within heavy metal contaminated soils.